2014
DOI: 10.1007/s00592-014-0672-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles derived from mesenchymal stem cells induce features of diabetic retinopathy in vitro

Abstract: We confirm that MSC-derived EV contribute to angiogenesis, showing that they may not only exert a direct stimulus to EC proliferation, but also induce pericyte detachment, thus leaving EC free to proliferate. In addition, we demonstrate a possible link between EV and the early stages of the pathogenesis of DR. Diabetic-like conditions may influence vessel remodelling during angiogenesis through EV paracrine signalling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 37 publications
6
41
0
Order By: Relevance
“…In agreement with a recent study showing that extracellular vesicles derived from the mesenchymal stem cells increased the blood–retina permeability in an in vitro model of diabetic retinopathy (Beltramo et al. ), one may discuss whether the BMSCs in our study had a similar, however, not statistically significant, effect. Although previous studies revealed that BMSCs could transdifferentiate into retinal pigment epithelium cells, photoreceptors in vitro and/or in vivo , and in vascular endothelial cells (Zhen‐Zhou et al.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with a recent study showing that extracellular vesicles derived from the mesenchymal stem cells increased the blood–retina permeability in an in vitro model of diabetic retinopathy (Beltramo et al. ), one may discuss whether the BMSCs in our study had a similar, however, not statistically significant, effect. Although previous studies revealed that BMSCs could transdifferentiate into retinal pigment epithelium cells, photoreceptors in vitro and/or in vivo , and in vascular endothelial cells (Zhen‐Zhou et al.…”
Section: Discussionsupporting
confidence: 93%
“…4B). In agreement with a recent study showing that extracellular vesicles derived from the mesenchymal stem cells increased the blood-retina permeability in an in vitro model of diabetic retinopathy (Beltramo et al 2014), one may discuss whether the BMSCs in our study had a similar, however, not statistically significant, effect. Although previous studies revealed that BMSCs could transdifferentiate into retinal pigment epithelium cells, photoreceptors in vitro and/or in vivo, and in vascular endothelial cells (Zhen-Zhou et al 2008), our study suggested that BMSCs were helpful for the regeneration and remodelling of injured vessels in retinopathy of prematurity models, without transdifferentiating into endothelial cells but by supporting a normal endothelial regeneration.…”
Section: Discussionsupporting
confidence: 93%
“…The primary involvement of hyperglycaemia in these events is well known (Beltramo & Porta ), with either direct or mediated actions (Beltramo et al. ; Mazzeo et al. ), but similar effects of hypoxia have been also recently described (Aplin & Nicosia ).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, EV added to EC/pericytes co‐cultures in matrigel promoted in vitro angiogenesis in a matrix metalloproteinase‐2‐dependent manner. Via these properties of microvessel remodeling, EV are an important element in the early stages of diabetic retinopathy pathogenesis …”
Section: Effects Of Ev On Endothelial Cellsmentioning
confidence: 99%